Perfil de metilação de genes relacionados à apoptose emameloblastomas - Sara Ferreira dos Santos Costa (2016)
Ameloblastoma is a benign epithelial odontogenic tumour. Unicystic and multicystic/solid types are more common. Apoptosis is a fundamental process in the tumour kinetics. The DNA methylation is an epigenetic modification that can regulates apoptosis-related genes. However, there is not data about methylation profile of apoptosis-related genes in ameloblastoma. The aim of the present study was to identify the methylation profile of apoptosis-related genes in the ameloblastoma and to investigate its possible role in the ameloblastoma pathogenesis. We used the restriction enzymatic digestion and real-time PCR array in 22 genes related to apoptosis. The genes showed differential methylation profile (TNFRSF25 and BCL2L11) were validated by genic expression. TNFRSF25 showed the lower levels of DNA methylation in ameloblastoma than dental follicle and its genic expression washigher in the ameloblastoma than normal tissues. BCL2L11 showed higher DNA methylation levels in unicystic ameloblastoma and dental follicle than multicystic ameloblastoma. The expression levels this gene also was higher in the tumours than controls. BCL2L11 or Bim is a proapoptotic Bcl-2 family member, but it was related to survival cellular in tumours. In other hand, TNFRSF25 or death receptor 3 (DR3) primarily to actives NF-kB and MAPKs pathways. In few cases, it can to result inapoptosis. In this study, the BCL2L11/Bim and TNFRSF25/DR3 high expressions can be related both apoptosis and cellular proliferation in ameloblastoma.